Different Effects of Total Bilirubin on 90-Day Mortality in Hospitalized Patients With Cirrhosis and Advanced Fibrosis: A Quantitative Analysis - Qiao, Liang; Tan, Wenting; Wang, Xiaobo; Zheng, Xin; Huang, Yan; Li, Beiling; Meng, Zhongji; Gao, Yanhang; Qian, Zhiping; Liu, Feng; Lu, Xiaobo; Shang, Jia; et al. (Frontiers in Medicine, 2021)
Introduction: Total bilirubin (TB) is a major prognosis predictor representing liver failure in patients with acute on chronic liver failure (ACLF). However, the cut-off value of TB for liver failure and whether the same cutoff could be applied in both cirrhotic and non-cirrhotic patients remain controversial. There is a need to obtain the quantitative correlation between TB and short-term mortality via evidence-based methods, which is critical in establishing solid ACLF diagnostic criteria. Methods: Patients hospitalized with cirrhosis or advanced fibrosis (FIB-4>1.45) 0were studied. TB and other variables were measured at baseline. The primary outcome was 90-day transplantation-free mortality. Multi-variable Cox proportional hazard model was used to present the independent risk of mortality due to TB. Generalized additive model and second derivate (acceleration) were used to plot the “TB-mortality correlation curves”. The mathematical (maximum acceleration) and clinical (adjusted 28-day transplantation-free mortality rate reaching 15%) TB cutoffs for liver failure were both calculated. Results: Among the 3532 included patients, the number of patients with cirrhosis and advanced fibrosis were 2592 and 940, respectively, of which cumulative 90-day mortality were 16.6%(430) and 7.4%(70) respectively. Any increase of TB was found the independent risk factor of mortality in cirrhotic patients, while only TB greater than 12mg/dL independently increased the risk of mortality in patients with advanced fibrosis. In cirrhotic patients, the mathematical TB cutoff for liver failure is 14.2mg/dL, with 23.3% (605/2592) patients exceeding it, corresponding to 13.3% and 25.0% adjusted 28-and 90-day mortality rate respectively. The clinical TB cutoff for is 18.1mg/dL, with 18.2% (471/2592) patients exceeding it. In patients with advanced fibrosis, the mathematical TB cutoff is 12.1mg/dL, 33.1% (311/940) patients exceeding it, corresponding to 2.9% and 8.0% adjusted 28- and 90-day mortality rate respectively; the clinical TB cutoff was 36.0 mg/dL, 1.3% (12/940) patients above it. Conclusion: This study clearly demonstrated the significantly different impact of TB on 90-day mortality in patients with cirrhosis and advanced fibrosis, proving that liver failure can be determined by TB alone in cirrhosis but not in advanced fibrosis. The proposed TB cutoffs for liver failure provides solid support for the establishment of ACLF diagnostic criteria.